Development of a High School Static Fluid Learning Video Based on Contextual Wetlands - Nurmahasih, Utari; Wiyono, Ketang (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to develop static fluid learning videos based on contextual wetland areas that are valid and practical. Learning videos were developed using R&D research design with the Rowntree development model, which consists of planning, development and evaluation stages. The evaluation stage in this research uses Tessmer formative evaluation only for the small group evaluation stage. Research data was collected through walkthroughs and questionnaires. Walkthrough data analysis uses the Aiken V Index, and the average percentage of questionnaire data is then converted to obtain conclusions about the validity and practicality of the video being developed. The results of the research concluded that the static fluid learning video for class included in the very high validity category. The percentage was 83.92% at the one-to-one evaluation stage and 81.50% at the small group evaluation stage, categorized as practical. These results indicate that the development of contextual wetland area-based high school static fluid learning videos is feasible for learning Wetland Environmental Physics.